Rheumatic Disease: Protease-Activated Receptor-2 in Synovial Joint Pathobiology - McCulloch, Kendal; McGrath, Sarah; Huesa, Carmen; Dunning, Lynette; Litherland, Gary; Crilly, Anne; Hultin, Leif; Ferrell, William R.; Lockhart, John C.; Goodyear, Carl S. (Frontiers in Endocrinology, 2018)
Protease-activated receptor-2 (PAR2) is one member of a small family of transmembrane, G-protein coupled receptors. These receptors are activated via cleavage of their N terminus by serine proteases (e.g. tryptase), unveiling an N terminus tethered ligand which binds to the second extracellular loop of the receptor. Increasing evidence has emerged identifying key pathophysiological roles for PAR2 in both rheumatoid arthritis (RA) and osteoarthritis (OA). Importantly, this includes both pro-inflammatory and destructive roles. For example, in murine models of RA, the associated synovitis, cartilage degradation and subsequent bone erosion are all significantly reduced in the absence of PAR2. Similarly, in experimental models of OA, the PAR2 disruption confers protection against cartilage degradation, subchondral bone osteosclerosis and osteophyte formation. This review focusses on the role of this receptor in arthritic disease and its potential as an important therapeutic target for the treating pain and joint degradation.